The influence of hormone replacement therapy on coagulation and fibrinolysis, with special regard to patients with type 2 diabetes - Telejko, Beata; Kinalska, Ida; Kowalska, Irina; Kinalski, Maciej (Menopause Review/Przegląd Menopauzalny, 2002)
Thrombosis plays a crucial role in the pathogenesis of both coronary heart disease and venous thromboembolic disease. Thus, in this article the effects of hormone replacement therapy on coagulation and fibrinolysis systems are reviewed and its potential impact on clinical outcomes is considered, with regard to the studies undertaken in women with type 2 diabetes mellitus.